ISSUES OF ACCOUNTING OF INCOME TAXATION SECURITIES OF BUSINESS ENTITIES - Qoriyeva Aziza Olimjon qizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
This article is about the securities market in the Republic of Uzbekistan, general information about them, updated laws, as well as the role of the securities market in the economy of the Republic of Uzbekistan.